The free-wheeling society: what values should be on the agenda and the role of the Christian education in the promotion of these values - Lategan, LOK (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
The focus of this article is the role that Christian ethics can play through the curricula of higher education institutions to combat the moral decline of society. The author reasons that there can be no such thing as neutral ethics and that every ethical belief is influenced by for instance religion, culture and circumstances. Ethics in the framework of post-modernism are thus disapproved of. This article shows that by integrating ethics in the curriculum, students as prospective employees and employers are prepared to live ethical. Finally an agenda is proposed of how ethical questions can be reflected therein. Failure to perform, be a team player and avoid gross transgressions such as stealing, lying, or drinking on the job was hazardous. Poor performance was the surest way of earning discipline. In contrast, unethical behaviour was rarely mentioned … Ethics was a matter of exit, rather than loyalty or voice (Badaracco & Webb 1995:13).